A Semiotics View Through Sexual Objectification of Women in TV Cigarette Commercials in Indonesia - Ralira Alstromer Osydea; Qomariyatus Sholihah; Intan Rahmawati (Wacana Journal of Social and Humanity Studies, 2023)
The woman is a human being who often becomes the meaning of beauty and can attract attention. But for women, it is a source of economic income. This assumption has an impact on women's self-exploitation practices, especially through sexual objectification, such as in TV cigarette commercials. Ironically, many of the commercials produced contradict society's ideal image and reality, and they can harm women. This study aims to analyze the sexual objectification of women in TV cigarette commercials in Indonesia. This study uses qualitative methods through semiotic analysis by John Fiske. The results of this study indicate that: 1) Women as sexual objects are represented as having a sexy dress style by exposing the chest, and the behavior also gestures show vulgar swaying that intends to seduce, then supported by disco music which reinforces the sexual objectification of female characters with evidence of male character responses that expressions and gestures seduced. 2) the meaning and ideology behind women being represented as sexual objects in this commercial is the phenomenon of sensuality technocracy to attract audiences in television commercials and negative developments in the media have pushed many women into an identity crisis. Keywords: woman representations, sexual objectification, tv commercial, semiotics, cigarette